BLOCKCHAIN TECHNOLOGY AND BITCOIN CRYPTOCURRENCY: HOW IT WORKS AND FEATURES - Doszhanov, Б.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Along with the socio-economic sphere, interest in Internet technologies in public-private partnerships, companies and institutions, organizations allows you to integrate blockchains into large infrastructure. This result can be achieved by giving the user access and changing internal database storage algorithms. The main feature of blockchain technology is that it is based on decentralization. In the case of using any means of protection, if it is possible to crack the database located on the server, then such a malfunction is not allowed in the blockchain. The article discusses the concepts of cryptocurrency, blockchain, and bitcoin, as well as the principles of their operation. Prospects for their development and large-scale impact on financial activities carried out via the Internet are presented. It also describes cryptocurrencies and the technologies and algorithms used in them.